The Impact of Technology Access Inequality and Digital Skill Disparities on Social Integration and Life Satisfaction in Indonesia - Judijanto, Loso; Nurwanto, Novi (Eastasouth Institute, 2024)
This study investigates the impact of technology access inequality and the digital skills gap on social integration and life satisfaction in Indonesia. Utilizing a quantitative approach, data were collected from 230 respondents using a structured questionnaire. The results were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to evaluate the relationships between variables. Findings indicate that both technology access inequality and digital skill disparities significantly influence social integration, which in turn affects life satisfaction. Notably, technology access inequality has the strongest direct effect on life satisfaction. This research underscores the necessity for targeted interventions to improve technology access and digital skills, which can enhance social cohesion and overall well-being in Indonesia.